A novel hierachically-nanostructured Pt/SiO2/Fe3O4 catalyst with high activity and recyclability towards hydrosilylation. Issue 100 (17th October 2016) - Zai, Huachao; Zhao, Yizhou; Chen, Shanyu; Wang, Rui; Ge, Lei; Chen, Changfeng; Li, Yujing
Abstract : Ultrafine Pt nanoparticles immobilized on the SiO2 /Fe3 O4 support show high activity towards the hydrosilylation. Abstract : Recycling of noble-metal-based catalysts remains difficult and limits their applications towards catalysis in organic synthesis reactions with high viscosity. This work demonstrates a magnetically responsive hydrosilylation catalyst with novel core–shell nanostructure, which can be recycled from highly viscous reaction solutions. The supporting material, with core–shell structure, incorporates a Fe3 O4 nanoparticle as the core coated with silica shell through reverse microemulsion approach to form SiO2 /Fe3 O4 nanoparticles which show superparamagnetic behavior. Ultrafine Pt NPs are facilely prepared and loaded on SiO2 shell via a simple hydrothermal protocol, forming Pt/SiO2 /Fe3 O4 catalyst. As-synthesized catalysts exhibit high catalytic activity towards the hydrosilylation of allyl polyether with low-hydro silicone oil. Despite the high viscosity of the reaction system, the catalyst dispersed in reaction solution shows superparamagnetic response upon the application of magnetic field and can be recycled up to 7 times without appreciable loss in the catalytic activity. This work demonstrates a highly efficient and recyclable catalyst to catalyze hydrosilylation reaction with high viscosity and proposes a new philosophy to design reusable catalyst for organic reaction.